Pengaruh Kepemilikan Institusional dan Kebijakan Dividen terhadap Nilai Perusahaan - Lihan Rini Puspo Wijaya (Jurnal Ilmiah ESAI, 2018)
A company is to get optimal profits that can improve the welfare of the owners and managers ofthe company. The main objective is reflected in the value of the company. This study aims toexamine whether institutional ownership influences dividend policy, whether dividend policyinfluences the value of the company, and whether institutional ownership and dividend policyinfluence the value of the company. The research population is companies that go public andare listed on the Indonesia Stock Exchange (IDX). The research sample was 94 companieswhose shares were included in the LQ 45 index that distributed dividends. The research periodis for 3 years, namely 2013 - 2015 using report data in the form of performance summariesissued by the Indonesia Stock Exchange (IDX) every August. Data testing uses classicalassumption testing and hypothesis testing using linear regression analysis. The results of thestudy show that institutional ownership does not affect dividend policy, dividend policy does notaffect the value of the company, and institutional ownership and dividend policy does not affectthe value of the company